Geometric Inspection in 3D Concrete Manufacturing: Comparison of Data Capturing Techniques - M. Maboudi; K. Mawas; M. Gerke (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Geometric quality inspection is an essential process in digital construction that provides insight into the conformity of the fabricated components to their designed models. It is even more important and challenging in modern 3D concrete printing processes where the realization of complex and intricate objects is possible. Using the right sensors for data capture is one of the key factors in the success and reliability of inspection results. Geometric inspection after printing makes it possible to update the digital model, adjust the next production step, or reject the fabricated objects if the deviation exceeds tolerances. This research investigates three different approaches, namely Terrestrial Laser Scanning (TLS), Terrestrial Photogrammetry (TP), and hand-held Structured Light Scanning (SLS), for the quality inspection of two medium-sized digitally fabricated concrete components. We compared the results of the data captured by each sensor with the respective other two sensors using cloud-to-mesh (C2M) distances. In all cases, the Root Mean Square Error (RMSE) is less than 1mm which is acceptable for the majority of applications within the realm of digital construction. Considering the geometric performance and other parameters –such as time, cost, and flexibility–to name a few, we conclude that hand-held SLS is an optimal choice for geometric inspection of small to medium-sized objects.